Prawo handlowe — między jednością a dualizmem prawa cywilnego. Uwagi z perspektywy prawa niemieckiego - Wiórek, Piotr Marcin (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The purpose of this article is to answer the question whether, after almost twenty years of the Polish Commercial Companies Code being in force, one should stick to the regulatory status quo which is an expression of the principle of unity of civil law in Polish law, or whether the situation is ripe to “redefine” commercial law and return to the principle of dualism in civil law. As a point of reference for this analysis, the discussion in the doctrine of German law was used to discuss the place and role of commercial law and the Commercial Code in the German civil law system. The comparative legal analysis carried out in the study leads to the conclusion that the mere formal separation of commercial and legal regulations as part of a separate codification in the form of the Commercial Code will not lead to a violation of the applicable principle of unity of civil law, provided that the regulation contained therein constitutes a special civil law regulation in relation to the Civil Code, supplementing and modifying the provisions of universal civil law.
Keywords: prawo handlowe; zasada jedności prawa cywilnego; dualizm prawa cywilnego; prawo polskie; prawo niemieckie; kodeks handlowy